Understanding the influence of fiber length on the High Volume Instrument™ measurement of cotton fiber strength. Issue 9 (June 2014) - Naylor, Geoffrey RS; Delhom, Christopher D; Cui, Xiaoliang; Gourlot, Jean-Paul; Rodgers, James
An earlier study confirmed the influence of cotton fiber length characteristics on the High Volume Instrument™ (HVI) strength measurement and devised a quantitative correction factor to compensate for the effect. The current paper investigated the validity of two important assumptions utilized in the previous study. Firstly, single fiber testing confirmed that the particular sample preparation method used to generate samples of different fiber length characteristics from a common cotton sliver did not introduce any inherent damage to the fibers (and so this could not be the explanation for the observed trend in measured fiber strength as a function of fiber length). Secondly, the positioning of the jaws relative to the beard in the HVI strength measurement was explored. This positioning was found to be quite variable for replicate measurements on the same cotton being a function of the size of each individual beard. The average positioning between the different samples was found to be similar and this validated the assumption and approach used previously for deriving the correction factor for that particular sample set. Characterizing the position of the jaws was extended using a wider range of cotton samples. The HVI positioning algorithm appears to not simply be a function of the size of the beard (i.e. the 'amount' parameter), but is also dependent on fiber length characteristics. It was also observed that the reported HVI elongation values displayed both a significant bias due to fiber length and also a dependence on the size of individual beards tested.